The PLANS model predicts recurrent strokes in patients with minor ischemic strokes - Zhi-Xin Huang; Haike Lu; Yi Lu; Yingyi Dai; Jianguo Lin; Zhenguo Liu (Scientific Reports)
Abstract Minor ischemic stroke (MIS) patients face significant risks of recurrent strokes, necessitating reliable predictive tools. This single-center retrospective study developed and validated a novel model for predicting 1-year stroke recurrence in MIS patients, defined as those with National Institutes of Health Stroke Scale scores < 4 within seven days of symptom onset. Among 218 patients (median age 64 years, 26.6% female), 32 (14.7%) experienced recurrent strokes within one year. Analysis of clinical and lifestyle variables identified physical activity, large artery stroke, admission NIHSS score, and smoking as significant predictors, forming the PLANS model. The model demonstrated superior predictive performance compared to the Essen model, with a higher C-index (0.780 vs. 0.556) and better calibration. Risk reclassification metrics showed significant improvements, with integrated discrimination improvement of 20.3%, continuous net reclassification improvement of 41.7%, and median risk score improvement of 18.5%. The PLANS model, incorporating both traditional and novel risk factors, provides a valuable tool for patient stratification and personalized secondary prevention strategies. External validation in diverse cohorts is warranted to confirm these promising results.